Effect of short light-dark cycles on young and adult TGR(mREN2)27 rats - Canal-Corretger, Maria Mercè; Witte, Klaus; Diez-Noguera, Antoni; Lemmer, Björn (Chronobiology international, 2001)
Animals placed under short light-dark (LD) cycles show a dissociation of their circadian rhythms. However, this effect has only been studied in Wistar rats and with the motor activity (MA) rhythm. Thus, in the present experiment, we studied in TGR(mREN2)27 (TGR) rats, a strain of hypertensive rats, the effect of a short LD cycle on the circadian rhythms of MA, heart rate (HR), and blood pressure (BP). Our aim was to investigate whether the exposure of TGR rats to a short LD cycle induced a dissociation of their circadian rhythms, to study the effect of short LD cycles on the development of the circadian rhythms of TGR rats, and to compare the effect of short LD cycles on young and adult TGR rats. One group of TGR rats was maintained under LD cycles of 22h periods (group G22). The progress in time of their rhythms was compared to that of TGR rats of the same age that had been kept under LD cycles of 24h periods (group G24). For the third point, the rhythms of a group of 5-week-old TGR rats kept under LD 22h cycles (young rats) were compared to those of a group of 11-week-old TGR rats (adult rats). Results showed that there is a dissociation of the circadian rhythms of all the variables monitored in TGR rats maintained under LD 22h cycles, independent of age. We have also found that group G22 showed a higher increase in BP with age and a higher mortality due to malignant hypertension compared to group G24. Finally, it seems that it is harder for young rats to entrain to short LD cycles than for adult rats, and young rats have a higher mortality due to malignant hypertension than adult rats. In conclusion, we demonstrated that short LD cycles produce a dissociation in the HR, BP, and MA circadian rhythms. The results of this experiment, compared to those previously obtained in Wistar rats, suggest that the light perception, the responses of the circadian system to light, or both are altered in the TGR rats.